Rotational flexural strength of cylindrical brittle specimens - Wereszczak, Andrew A.; Steiner, Emily F.; Jadaan, Osama M.; Wiles, Randy H.; Kuwik, Brett S. (Journal of the American Ceramic Society, 2022)
Conventional static flexural strength testing of brittle cylindrical rods only subjects a small fraction of the entire specimen's area or volume to the maximum tensile stress. Thus, a nonconservative measured strength likely results since most flaws on the surface or in the bulk are not subjected to a sufficiently high tensile stress that can cause fracture. To mitigate this, a rotational flexural tester and corresponding test method were developed whereby rotation and monotonically increasing three‐point flexure were superimposed to investigate fracture response of solid glass cylinders. This combination of rotation and flexure subjects more area and volume of a cylindrical test specimen to tensile stress than a standard static (nonrotating) flexural test. As anticipated, failure stresses were lower for the rotational flexural test. Expressions for effective area and volume are provided for rotating solid rods and tubes subjected to three‐point, four‐point, uniform, and uniformly distributed load bending configurations.